2009
DOI: 10.1103/physrevd.79.053005
|View full text |Cite
|
Sign up to set email alerts
|

Unparticle effects in neutrino telescopes

Abstract: Recently H.Georgi has introduced the concept of unparticles in order to describe the low energy physics of a nontrivial scale invariant sector of an effective theory. We investigate its physical effects on the neutrino flux to be detected in a kilometer cubic neutrino telescope such as IceCube. We study the effects, on different observables, of the survival neutrino flux after through the Earth and the regeneration originated in the neutral currents. We calculate the contribution of unparticle physics to the n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(21 reference statements)
1
7
0
Order By: Relevance
“…Furthermore, unparticle contributions to the neutrino-nucleon cross section and its influence on the neutrino flux expected in a neutrino telescope such as IceCube have been reported in Ref. [58].…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, unparticle contributions to the neutrino-nucleon cross section and its influence on the neutrino flux expected in a neutrino telescope such as IceCube have been reported in Ref. [58].…”
Section: Introductionmentioning
confidence: 95%
“…Dubbed "unparticle physics" because of the non-intuitive phase space structure, its introduction has caused a flurry of research into modifications to known physics and post-TeV predictions. Accelerator phenomenology has been the main emphasis in the literature [3][4][5][6][7][8][9][10] [11,12], but astrophysical/cosmological [13][14][15][16][17][18] [19][20][21][22][23][24] [ [25][26][27], low to ultra-high neutrino phenomenology [28][29][30][31][32][33][34][35] and general quantum field theory [36][37][38][39][40][41] [42,43] applications have been of extreme importance as well.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerably less literature dealing with bounds on the exotic quark masses [58,59], which in general depend on the masses of the heavy gauge bosons. From the search for supersymmetric particles at the Tevatron, a bound on the D quark mass of about 300 GeV was obtained for m Z ′ around 1 TeV [58].…”
Section: A Constraints On the Model Parametersmentioning
confidence: 99%
“…From the search for supersymmetric particles at the Tevatron, a bound on the D quark mass of about 300 GeV was obtained for m Z ′ around 1 TeV [58]. Another constraint was obtained in [59] from the experimental data on the Z →bb decay and electroweak precision measurements at the Z pole: it was found that the T quark mass is bounded into the 1500-4000 GeV interval for m Y −− around 700 GeV.…”
Section: A Constraints On the Model Parametersmentioning
confidence: 99%